DISASTER PREPAREDNESS SCHOOL (SSB) TRAINING FOR TEACHERS AND STUDENTS AT EARLY CHILDHOOD EDUCATION PROGRAMS (PAUD) SUB-DISTRICT CIWANDAN, CILEGON – BANTEN [PELATIHAN SEKOLAH SIAGA BENCANA (SSB) BAGI GURU-GURU DAN SISWA-SISWI LEMBAGA PAUD DI CIWANDAN, KOTA CILEGON – BANTEN] - Rudy Pramono; Yubali Ani; Chandra Han; Ashiong P. Munthe; Manek Ndoloe (Universitas Pelita Harapan, 2019)
Disaster Preparedness School (SSB) is an effort to build school preparedness against disasters in order to raise awareness of all elements in the education sector both individually and collectively in schools and the school environment before, during, and after a disaster occurs. The training was conducted at Widuri PAUD located in Kubang Welut Village, Ciwandan Sub-District, Cilegon City. Method of training is simulations. Simulations in disaster management can measure and improve one's readiness in facing of disasters. In this training needed the support of principals, teachers, staff, and all parties in the school and active participation of all students. There are two stages in this exercise and simulations. First, to learn about the threat of danger, to find out whether schools are safe from the threat of earthquake disasters. According to the circumstances and location of each school, students must learn, pay attention to the situation and location of the school guide by the teacher. Second, disaster simulation training, to increase knowledge about ways to do early warning and rescue when a disaster occurs. Simulation exercises is to shape attitudes, togetherness, cohesiveness, and mutual help. In this exercise the teacher, the staff, parents are guided to increase the awareness and develop skills of students in rescuing in the moment of disaster. In order for the simulation to succeed well, this exercise needs to be planned, prepared, carried out, and evaluated repeatedly.Bahasa Indonesia Abstrak: Sekolah Siaga Bencana (SSB) merupakan upaya membangun kesiapsiagaan sekolah terhadap bencana dalam rangka menggugah kesadaran seluruh unsur-unsur dalam bidang pendidikan baik individu maupun kolektif di sekolah dan lingkungan sekolah baik itu sebelum, saat, maupun setelah bencana terjadi. Kegiatan pelatihan siaga bencana pada anak-anak ini dilakukan di PAUD Widuri yang berlokasi di Kelurahan Kubang Welut, Kecamatan Ciwandan, Kota Cilegon. Metode pelatihan yang digunakan adalah dengan simulasi. Simulasi di dalam manajemen bencana dapat mengukur dan meningkatkan kesiapan seseorang dalam menghadapi bencana. Dalam pelatihan ini diperlukan dukungan kepala sekolah, guru, staf, dan semua pihak di lingkungan sekolah dan partisipasi aktif siswa. Ada dua tahap dalam latihan dan simulasi ini. Pertama, menyampaikan materi kepada para guru tentang ancaman bahaya, untuk mengetahui apakah sekolah aman dari ancaman bahaya bencana gempa bumi. Sesuai keadaan dan lokasi sekolah, siswa/i agar dapat belajar, memperhatikan keadaan dan lokasi sekolah dengan bimbingan para guru. Kedua, latihan simulasi menghadapi bencana: untuk meningkatkan pengetahuan tentang cara-cara melakukan peringatan dini dan penyelamatan ketika terjadi bencana. Latihan simulasi bertujuan untuk membentuk sikap, kebersamaan, kekompakan dan saling tolong menolong. Dalam latihan ini dibimbing oleh guru, staf, dan orang tua untuk meningkatkan kesadaran dan keterampilan siswa dalam melakukan penyelamatan bila terjadi bencana. Agar latihan simulai dapat berhasil dengan baik, maka latihan perlu direncanakan, dipersiapkan, dilaksanakan, dan dievaluasi secara berulang-ulang.